Long-Term Predictors of Disease Free Survival (DFS) in Ovarian Cancer Sensitive to Platinum Based Chemotherapy - selvyana, Dita Ria; Kurnianda, Johan (Universitas Muhammadiyah Yogyakarta, 2019)
Until now, there has been progress in the treatment of ovarian cancer, but ovarian carcinoma is still a cause of high mortality. Various factors have been known to be associated with a poor prognosis, such as the absence of symptoms, lack of an effective screening tool, diagnosis of the disease that was only detected after an advanced stage, high recurrence of disease resistant to chemotherapy. There are more than 70% of cases detected in advanced stage, with long-term survival of only 15-30%; while those detected in early stages, the survival reaches 90%. The recurrence risk of IIIC stage disease is as high as 40% -50%. However, there is a small group of patients who can recover after standard therapy. There is variability in the recurrence-free period and survival, so it is difficult to predict the outcome with certainty. Ovarian cancer patients with the same characteristics can show a different prognosis, related to high molecular heterogeneity of tumor genetics. We report a rare case that is a 56-year-old woman who has experienced a 5-year free disease after complete remission after standard chemotherapy from stage IIIC ovarian cancer. The disease-free period of up to 5 years after therapy may be related to factors that can be predictors of prognosis, such as age at diagnosis, body mass index, physical performance, cancer cell biology, and the success of surgical response and chemotherapy in these patients.